Inhalation of ZnO Nanoparticles: Splice Junction Expression and Alternative Splicing in Mice - Rossner, Pavel; Vrbova, Kristyna; Strapacova, Simona; Rossnerova, Andrea; Ambroz, Antonin; Brzicova, Tana; Libalova, Helena; Javorkova, Eliska; Kulich, Pavel; Vecera, Zbynek; Mikuska, Pavel; Coufalik, Pavel; et al. (Toxicological sciences, 2019)
Despite the wide application of nanomaterials, toxicity studies of nanoparticles (NP) are often limited to in vitro cell models, and the biological impact of NP exposure in mammals has not been thoroughly investigated. Zinc oxide (ZnO) NPs are commonly used in various consumer products. To evaluate the effects of the inhalation of ZnO NP in mice, we studied splice junction expression in the lungs as a proxy to gene expression changes analysis. Female ICR mice were treated with 6.46 × 104 and 1.93 × 106 NP/cm3 for 3 days and 3 months, respectively. An analysis of differential expression and alternative splicing events in 298 targets (splice junctions) of 68 genes involved in the processes relevant to the biological effects of ZnO NP was conducted using next-generation sequencing. Three days of exposure resulted in the upregulation of IL-6 and downregulation of BID, GSR, NF-kB2, PTGS2, SLC11A2, and TXNRD1 splice junction expression; 3 months of exposure increased the expression of splice junctions in ALDH3A1, APAF1, BID, CASP3, DHCR7, GCLC, GCLM, GSR, GSS, EHHADH, FAS, HMOX-1, IFNγ, NF-kB1, NQO-1, PTGS1, PTGS2, RAD51, RIPK2, SRXN1, TRAF6, and TXNRD1. Alternative splicing of TRAF6 and TXNRD1 was induced after 3 days of exposure to 1.93 × 106 NP/cm3. In summary, we observed changes of splice junction expression in genes involved in oxidative stress, apoptosis, immune response, inflammation, and DNA repair, as well as the induction of alternative splicing in genes associated with oxidative stress and inflammation. Our data indicate the potential negative biological effects of ZnO NP inhalation.
Keywords: exprese genu; oxidační stres; Gene Expression; Inflammation; splice junction expression; plíce; Nanoparticles; nanočástice; aplikace inhalační; Mice, Inbred ICR; oxid zinečnatý; zánět; DNA Repair; Lung; oprava DNA; alternative splicing; zinc oxide nanoparticles; Animals; buněčná imunita; alternativní sestřih; ženské pohlaví; zvířata; Cell Cycle; Immunity, Cellular; myši; myši inbrední ICR; apoptóza; Alternative Splicing; Zinc Oxide; buněčný cyklus; Mice; Female; Oxidative Stress; Administration, Inhalation; inhalation; Apoptosis